Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge handbooks in philosophy, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice--one of the most important and ground-breaking subjects to have emerged in philosophy in recent years--refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales